PERAN KEPEMIMPINAN PARTISIPATIF DALAM MENINGKATKAN KOLABORATIF MASYARAKAT PADA PROGRAM “SUMBAR BERSATU” UNTUK PENGELOLAAN SAMPAH DI SUMATERA BARAT - Iqbal Fahrezi; Syamsir Syamsir; Riffa Dwi Berliana; Filzah Sabrila; Elsa Oktaviani; Huriyatul Husna; Giva Febria Esa Rahman (Al-Hisbah Jurnal Ekonomi Syariah, 2025)
This research was motivated by the large amount of waste in West Sumatra, which was then developed by the United West Sumatra program in managing waste. The purpose of this study is to analyze the role of participatory leadership in increasing community collaboration in the "United West Sumatra" program which is focused on waste management in West Sumatra Province, especially in case studies at the West Sumatra Environment Agency. A qualitative approach is used with the case study method, where data is obtained through in-depth interviews, participatory observation, and documentation. The results of the study show that participatory leadership implemented by the Environment Agency plays a significant role in encouraging active community involvement, increasing the sense of collective responsibility, and strengthening synergy between the government and citizens in waste management. Factors such as two-way communication, openness to input, and community empowerment are key elements in the effectiveness of participatory leadership, including in the success of the United West Sumatra program. The results of the program seem to have more impact because of the shrinking waste and also the increasing number of effective waste management places. The implications of this study inform that the United West Sumatra program must continue to be carried out by the government by using a good leadership style and moving forward in managing and overcoming waste in West Sumatra.